Beyond Awareness: Investigating the Disconnect Between Oral Health Knowledge and Caries Experience (DMF-T) in Indonesian Primary Schoolchildren (Open Access Indonesian Journal of Medical Reviews, 2025)
Dental caries remains a significant public health problem among Indonesian children, impacting their quality of life and development. While oral health knowledge is considered crucial for prevention, its direct impact on caries experience, particularly in specific Indonesian contexts, requires further investigation. This study aimed to assess the relationship between oral health knowledge and caries experience (DMF-T index) among grade 2 students at an Islamic Integrated Primary School in Indonesia. A cross-sectional study was conducted involving 85 second-grade students selected via purposive sampling. Oral health knowledge was assessed using a validated, structured questionnaire covering topics like tooth brushing importance, frequency, caries causes, and prevention. Caries experience was measured using the DMF-T (decayed, missing, filled teeth) index through clinical examinations performed by trained dental personnel. Data were analyzed using descriptive statistics and the Chi-square test to determine the association between knowledge level (categorized as low or sufficient) and DMF-T status (categorized as low, moderate, or high), with significance set at p
Keywords: Dental caries; DMF-T index; Health education; Oral health knowledge; Primary school children